2012
DOI: 10.3389/fphys.2012.00356
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Nervous System Function and Aerobic Capacity in Type 1 Diabetes

Abstract: Impaired cardiovascular autonomic nervous system (ANS) function has been reported in type 1 diabetes (T1D) patients. ANS function, evaluated by heart rate variability (HRV), systolic blood pressure variability (SBPV), and baroreflex sensitivity (BRS), has been linked to aerobic capacity (VO2peak) in healthy subjects, but this relationship is unknown in T1D. We examined cardiovascular ANS function at rest and during function tests, and its relations to VO2peak in T1D individuals. Ten T1D patients (34 ± 7 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
1
15
1
1
Order By: Relevance
“…Hagglund et al. () investigated HRV in 10 T1D and found no association between resting HRV metrics and V̇ O 2max in this group. However, the absence of association was assessed with a small sample size ( n = 10) and with second derivative frequency‐domain metric (i.e., derived from TP); HF power.…”
Section: Introductionmentioning
confidence: 77%
“…Hagglund et al. () investigated HRV in 10 T1D and found no association between resting HRV metrics and V̇ O 2max in this group. However, the absence of association was assessed with a small sample size ( n = 10) and with second derivative frequency‐domain metric (i.e., derived from TP); HF power.…”
Section: Introductionmentioning
confidence: 77%
“…However, Hägglund et al (33) found no statistically significant differences for the SD1 index in young adults with DM1 at rest. The authors suggested this may be related to the small sample size used in the study or the fact that individuals analyzed were under adequate control and treatment of blood glucose, which could mask the alterations generated by diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the Poincaré plot qualitative analysis, which allows a nonlinear assessment of ANS (16,33,35), was observed a less dispersion of points for the DM1 group compared with the control group. This low dispersion pattern of RR reflects a reduction in HRV, indicating loss of ANS complexity for these individuals (16).…”
Section: ) Rr(n) (Ms) On the X-axis And Rr (N+1) (Ms) On The Y-axismentioning
confidence: 99%
“…The analysis software used was the GraphPad InStat ® . The sampling calculation was based on the correlation value between HRV and VO 2 found in the study by Hägglund et al 20 . Thus, the correlation coefficient value used in this statistical procedure was of 0.64, a statistical power of 80% and alpha of 0.05 was considered.…”
Section: Discussionmentioning
confidence: 99%